2020
DOI: 10.1007/s40430-020-02412-4
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of simplified models to predict soot formation in laminar flames

Abstract: Soot formation and radiation are important aspects for combustion problems. In this work, numerical simulations of ethylene coflow laminar flames are used to evaluate soot formation and radiation processes under different modeling approximations. Priority was given for models that were capable of producing detailed information with reduced computational requirements. So, the objective of this work is to show and quantify the importance of heat loss by gas and soot radiation and to quantitatively show the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…also evaluated using the models used in the present work. The results not included here for the sake of brevity indicated that the soot volume fraction fields are completely different to the ones discussed in the original work (Zimmer and Pereira, 2020). This happened even though the soot source terms regarding nucleation, surface growth and oxidation showed similar trends.…”
Section: Results Validationmentioning
confidence: 73%
See 1 more Smart Citation
“…also evaluated using the models used in the present work. The results not included here for the sake of brevity indicated that the soot volume fraction fields are completely different to the ones discussed in the original work (Zimmer and Pereira, 2020). This happened even though the soot source terms regarding nucleation, surface growth and oxidation showed similar trends.…”
Section: Results Validationmentioning
confidence: 73%
“…So major differences found in the temperature fields for this case could be originated by this fact. In addition, in order to assess model formulations and their influence on soot predictions when using semi-empirical soot models, the laminar flame studied by Zimmer and Pereira (2020) was…”
Section: Results Validationmentioning
confidence: 99%
“…where is the diffusion coefficient for laminar flames, and is the r-th statistical moment source term. Following the work by Zimmer and Pereira [42], a constant value of 10 -6 m 2 /s 2 is considered for . Source terms are defined in turn in terms of the soot formation and evolution mechanisms,…”
Section: Soot Modelingmentioning
confidence: 99%